Molecular imaging in hypertrophic cardiomyopathy: an exploratory study with 2-[18F]FDG and [13N]NH3 - Maria João Ferreira; Patrícia Marques-Alves; Rodolfo Silva; Andreia Gomes; Antero Abrunhosa; Miguel Castelo-Branco; Wael Jaber; Lino Gonçalves (EJNMMI Research)
Abstract Background Hypertrophic Cardiomyopathy (HCM), a genetic disorder with diverse phenotypes, is associated with risks of heart failure and sudden cardiac death. While the condition involves multiple pathological pathways, including myocardial inflammation, increased workload, myocyte disarray, apoptosis, and fibrosis, the role of molecular imaging via PET-CT remains unexplored in this context. This study aimed to investigate the relationship between myocardial metabolism and perfusion using PET-CT in patients with non-obstructive HCM (NOHCM). Results Myocardial perfusion and metabolism were assessed using PET-CT with [13N]NH3 and 2-[18F]FDG uptake, respectively, in 30 NOHCM patients. Baseline measurements included maximal myocardial wall thickness (MMWT), left atrial volume (LAV), NT-proBNP levels, and the sudden cardiac death (SCD) risk score. Increased 2-[18F]FDG uptake (Target to Background Ratio – TBR ≥ 1.1) was detected in 53% of patients, with an average TBR of 1.4 ± 0.5. The inflammatory pattern involved 11.8 ± 17.2% of the left ventricle (LV) and correlated with MMWT (rho = 0.49, p = 0.009), LAV (rho = 0.39, p = 0.04), and NT-proBNP levels (rho = 0.63, p = 0.003). The maximum TBR within the LV correlated with MMWT (rho = 0.53, p = 0.004), NT-proBNP (rho = 0.70,p = 0.0008), and the SCD risk score (rho = 0.38,p = 0.04). Additionally, the fibrotic (scar) pattern, involving 10.3 ± 10.2% of the LV, correlated with the SCD score (rho = 0.38,p = 0.04). Conclusion In patients with NOHCM, PET-CT imaging provides valuable insights into myocardial metabolism and fibrosis, which are closely associated with myocardial hypertrophy, left ventricular dysfunction, and the risk of sudden cardiac death.